2016
DOI: 10.1002/srin.201600319
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Solidification in Continuous Casting Round Billet with Mold Electromagnetic Stirring (M-EMS)

Abstract: A fully couple flow of molten steel, heat transfer, and solidification in the mold region of a continuous casting round billet under mold electromagnetic stirring (M-EMS) are investigate with computational tools of fluid flow and electromagnetic simulations. A finite element model is employed to simulate the electromagnetic stirrer in the mold and calculate the Lorenz force distribution. The Lorenz forces are applied as a source term in the Navier-Stokes equations of the fluid flow model, which was solved thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 20 publications
2
51
0
Order By: Relevance
“…Two methods to realize a swirling flow or rotational flow during the steel casting have been intensively studied, namely, the swirling flow SEN method [26][27][28][29][30][31][32][33][34] and the mold-electromagnetic stirring (MEMS) method. [35][36][37][38] When using a swirling flow SEN, the penetration depth of the SEN outlet flow in mold was found to decrease. [28] The stability of the steel flow in the mold was enhanced and the defects on the slab surface were effectively reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two methods to realize a swirling flow or rotational flow during the steel casting have been intensively studied, namely, the swirling flow SEN method [26][27][28][29][30][31][32][33][34] and the mold-electromagnetic stirring (MEMS) method. [35][36][37][38] When using a swirling flow SEN, the penetration depth of the SEN outlet flow in mold was found to decrease. [28] The stability of the steel flow in the mold was enhanced and the defects on the slab surface were effectively reduced.…”
Section: Introductionmentioning
confidence: 99%
“…[36] Therefore, the use of a swirling flow or a rotational flow during metal castings is becoming an important way to produce high-quality steels. However, previous studies [26][27][28][29][30][31][32][33][34][35][36][37][38] of swirling flows during steel castings mainly focused only on the influence on the steel flow itself. Furthermore, previous studies focusing on the inclusion behavior in steel flows have mostly been carried out for conventional continuous casting processes, where no rotational steel flow phenomena exist in the horizontal cross sections of the SEN or the mold.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Trindade et al [8] reported the inclusion trajectory and removal law by coupling magnetic field, flow field, and particle transport. [8][9][10][11][12][13][14][15] Trindade et al [8] reported the inclusion trajectory and removal law by coupling magnetic field, flow field, and particle transport.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35] This means that the technologies for a swirling flow in the SENs has the potential to replace the electromagnetic stirring in molds. [10,11,36,37] The swirling flow inside the SEN was probably first proposed by Yokoya et al [29] in 1994. Thereafter, many studies have been carried out to investigate the steel flow phenomena in molds, for both the slab and the billet casting, using a swirling flow in SENs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the possibility of producing a strong swirling flow intensity using this new tundish design remains further to be investigated both experimentally and numerically, which is important for implementing new designs in industry, and is important for its potential to replace the electromagnetic stirring in molds. [10,11,36,37] In a swirling flow in SEN, a large velocity gradient normally exists in the radial direction of a cross section of the SEN, especially in the turbulent boundary layer. Anisotropy in the turbulent fluctuations may exist in such flow situations.…”
Section: Introductionmentioning
confidence: 99%